Production and characterization of monoclonal antibodies against the lethal factor component of Bacillus anthracis lethal toxin. - Little, S F (1990)
The lethal toxin of Bacillus anthracis consists of two components, protective antigen and lethal factor. Protective antigen is cleaved after binding to cell receptors, yielding a receptor-bound fragment that binds lethal factor. Sixty-one monoclonal antibodies to the lethal factor protein have been characterized for specificity, antibody subtype, and ability to neutralize lethal toxin. Three monoclonal antibodies (10G3, 2E7, and 3F6) neutralized lethal toxin in Fisher 344 rats. However, in a macrophage cytolysis assay, monoclonal antibodies 10G3, 2E7, 10G4, 10D4, 13D10, and 1D8, but not 3F6, were found to neutralize lethal toxin. Binding studies showed that five of the monoclonal antibodies that neutralized lethal toxin in the macrophage assay (10G3, 2E7, 10G4, 10D4, and 13D10) did so by inhibiting the binding of lethal factor to the protective antigen fragment bound to cells. Monoclonal antibody 1D8, which was also able to neutralize lethal toxin activity after lethal factor was prebound to cell-bound protective antigen, only partially inhibited binding of lethal factor to protective antigen. Monoclonal antibody 3F6 did not inhibit the binding of lethal factor to protective antigen. A competitive-binding enzyme-linked immunosorbent assay showed that at least four different antigenic regions on lethal factor were recognized by these seven neutralizing hybridomas. The anomalous behavior of 3F6 suggests that it may induce a conformational change in lethal factor. Differences in neutralizing activity of monoclonal antibodies were related to their relative affinity and epitope specificity and the type of assay.